A hybrid compass mechanism combining radical pairs and magnetite crystals - P. J. Hore (Proceedings of the National Academy of Sciences, 2026)
That night-migratory songbirds have a magnetic compass sense is undisputed. The nature of the sensor, however, is far from certain. The two leading hypotheses are organic radical pairs in cryptochrome flavoproteins and crystals of inorganic magnetic minerals such as magnetite. Here, we propose a magnetoreception mechanism that combines radical pair chemistry with magnetite nanoparticles. Instead of directly detecting the tiny dependence of a radical pair reaction on the direction of the Earth’s (~50 μT) magnetic field, this hybrid sensor uses a magnetic particle to amplify the Earth’s field. Directional information is thereby encoded in the response of nearby radical pairs to the intensity of a much stronger (~5 mT) magnetic field. The result is a magnetoreceptor with potentially 10 to 100-fold greater sensitivity than afforded by radical pairs alone.